Analysis of Islamic Educational Policy: Thailand Case Study - Harahap, Koiy Sahbudin; Rajab, Khairunnas; Helmiati, Helmiati; Sawaluddin, Sawaluddin (JURNAL AL-TANZIM, 2022)
This study aims to analyze the policy of Islamic education in Thailand. The method used is a case study qualitative method. The data collection technique is done through interviews, observation, and documentation. The data analysis technique used consists of three co-occurring activities: data reduction, data presentation, conclusion drawing/verification. The results showed that; Islamic education policies in the field of curriculum, namely policies carried out by requiring general subjects such as mathematics, science, geography; Islamic education policy regarding the Thai language, namely using and developing the Thai language in student learning; Islamic Education Policy regarding teachers, namely providing training for teachers and education personnel to improve their abilities and knowledge. This research implies that it can be used as input for the government, stakeholders, leaders, teachers in making policies so that the quality of education is more qualified and able to compete with other countries.